Proteinuria and risk of stroke in patients with hypertension: The Kailuan cohort study. Issue 4 (6th April 2018) - Wang, Anxin; Dai, Liye; Su, Zhaoping; Chen, Shuohua; Li, Junjuan; Wu, Shouling; Wang, Yongjun; Wang, Yilong
Abstract : Proteinuria is associated with stroke, but the effects of changes in proteinuria on stroke risk are not well understood in the hypertensive population. This study examined whether proteinuria changes across 2‐year assessments were associated with incident stroke in individuals with hypertension. We used visit data from 24 300 participants with hypertension of the Kailuan study who were stroke free at baseline. Based on the baseline and 2‐year dipstick screening results, participants were classified as having no, remittent, incident, or persistent proteinuria. The relationship between proteinuria and stroke was analyzed using Cox proportional‐hazards models after adjusting for potential variables. During a median of 6.89‐year follow‐up, we identified 1197 people with stroke. Compared to those with no proteinuria, stroke risk was significantly increased in participants with incident (hazard ratio [HR] 1.41, 95% CI, 1.05‐1.77) and persistent proteinuria (HR 1.49, 95% CI, 1.25‐1.89) after adjustment for other factors, which was consistent in ischemic stroke and intracerebral hemorrhage. No interaction was found between changes of proteinuria and diabetes mellitus in the hypertensive population. Changes in proteinuria exposure, particularly persistent proteinuria, play a role in reflecting the risk of stroke in patients with hypertension.